Adsorption of total petroleum hydrocarbon in groundwater by KOH-activated biochar loaded double surfactant-modified nZVI - Ji, Caiya; Yin, Hongyang; Zhou, Meichun; Sun, Zhao; Zhao, Yuan; Li, Liangzhong (Frontiers in Materials, 2023)
Modified corn stalk biochar (SBC) was synthesized through high-temperature carbonization and KOH activation. Subsequently, the iron/carbon composite PN-nZVI@SBC (PNMSBC) was prepared by loading nano zero-valent iron modified with dual surfactants, and it was adopted to adsorb total petroleum hydrocarbons (TPH) in groundwater. The physical and chemical properties, surface patterns, and elemental mapping of PNMSBC particles were analyzed using SEM, EDS, TEM, XRD, BET, and FTIR spectroscopy. Kinetics and isotherm tests were performed to evaluate the adsorption properties of the composites. TPH adsorption was dependent on ionic strength, initial TPH concentration, as well as pH. The adsorption mechanism combining XPS and EPR spectroscopy was explored. The characterization results by SEM and TEM showed that the particle size of nZVI particles modified by surfactants became smaller, and the dispersibility was enhanced. The characterization results by XRD and FTIR confirmed the successful preparation of the composites. The BET results showed that MSBC and PNMSBC were mesoporous structures. The characterization results indicated that Polyvinylpyrrolidone (PVP) and Sodium oleate (NaOA) inhibited the oxidation of nZVI while effectively improving its reactivity. The result of the experiments on adsorption showed that the removal of TPH by PNMSBC followed Freundlich isotherm and pseudo-second-order kinetic models, thus suggesting that the main adsorption processes comprise chemisorption and multilayer heterogeneous adsorption. The adsorption capacity of PNMSBC was increased by the abundance of macro and microporous structures. To be specific, a maximum Langmuir adsorption capacity (qm) was achieved as 75.26 g/g. The result of batch experiments indicated that PNMSBC continuously removed considerable TPH under a wide pH range from 2 to 6. The adsorption mechanism of PNMSBC includes surface adsorption, oxidation, complexation, and electrostatic interaction. In brief, PNMSBC has a promising application for the adsorption of TPH in groundwater remediation.